Daily rescued raw temperature and pressure, measured in Bahía Blanca from 1960 to 1979 - Susan Gabriela Lakkis (PANGAEA, 2022)
The international Atmospheric Circulation Reconstructions over the Earth (ACRE) initiative works to recover global climate history and build an accessible databank, with data from the past 250 years of terrestrial and marine surface. Argentina is part of that effort with ACRE Argentina recovering data from various sources that have been recorded throughout the country since the 19th century. We present here weather observations transcribed from the original records into digital form and taken every day during the years 1860-1879 at Bahía Blanca (Lat 38.75°S, Lon 62.25°O). The digitization was carried out through the project Meteorologum ad Extremum Terrae (MET) launched in the Zooniverse interface, which is currently working with near 900 citizen scientist volunteers per day (https://www.zooniverse.org/projects/acre-ar/meteororum-ad-extremum-terrae). The present analysis corresponds to data retrieved from the collection "Anales de la Oficina Meteorológica Argentina" and contains information on means daily temperature in °C and mean daily pressure values in mmHg. The data will serve as a useful foundation to further examine historical climate variability in the Argentina.